Análisis jurídico y doctrinario de la repatriación y el indulto como medidas empleadas por el gobierno para bajar la sobrepoblación carcelaria - Villalta Carrera, Yulissa Nohelia (2023)
The present work of curricular integración prior to opting for the title of Lawyer is entitled: "Legal and doctrinal analysis of repatriation and pardon as measures used by the government to reduce prison overcrowding", arises from the interest in analysing in detail the overpopulation of prisons in Ecuador, which despite having decreed presidential pardons and repatriations during the years 2021, 2022 and 2023 as measures to reduce the rate of overcrowding, has not been given results in its entirety, but in a small proportion. In May 2021, Guillermo Lasso assumed the presidency and had to deal with three of the four massacres that occurred during the first seven months of his mandate. During these months, the government adopted a discourse that blamed drug gangs directly for prison violence, ignoring the lack of control, inhumane conditions and the state's responsibility for the situation. To control the crisis, the government announced a comprehensive set of measures. None of them are aimed at changing the structural conditions in prisons. In fact, so far, the announced pardon plan, which could reduce prison overcrowding, has not been implemented, nor have the necessary resources been allocated to rehabilitate the infrastructures affected by the bloody clashes, nor have investments been made to improve the living conditions of the (PPL) persons deprived of their liberty. While increased resources are planned for 2022 (an allocation of $124.4 million is planned), most of this money (76%) will go to pay salaries in the National System of Care for Persons Deprived of their Liberty. In the development of the present work of curricular integration, materials and methods were used, which were mentioned in the project of the curricular integration work, indicating in this the elaboration of interviews and surveys to legal professionals who provided useful and relevant information for the development of this work and to reach the conclusion of the need to raise a legal proposal as a result of the analysis and interpretation of statistical data of Ecuador, which is a country of 17 million inhabitants, which has a prison population of 39,000 people. Its prison system is made up of 53 prisons, which together have the capacity to hold some 30,000 people, but which nevertheless hold almost 10,000 more.